Renal failure following insulin purging in atypical anorexia nervosa and type 1 diabetes mellitus - Rometsch, Caroline; Guthoff, Martina; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2023)
Objective Anorexia nervosa (AN) and atypical anorexia nervosa (AAN) are severe and complex eating disorders that can be prevalent among individuals with type 1 diabetes mellitus (T1DM). Insulin purging, characterized by the intentional underuse / omission of insulin to control weight, is under-recognized in medicine and is a purging strategy of patients with AN or AAN and comorbid T1DM. Often, this can lead to renal failure, necessitating a (pancreas-) kidney transplantation. This article presents a comprehensive overview of the interplay between AN/AAN and T1DM and summarizes the evidence in literature. Methods A narrative review is presented on basis of a detailed case study of a 32-year-old female with end-stage renal failure seeking (pancreas-) kidney transplantation displaying etiology, diagnosis, comorbidities, complications, and treatment of AN and AAN with emphasis on those patients with T1DM. Results Insulin purging in patients with AN/AAN and coexisting T1DM can exacerbate T1DM complications, including accelerating the onset of end-stage renal failure. A multidisciplinary approach including nutrition treatment and psychotherapeutic techniques was considered necessary for treatment, focusing on psychosomatic in-patient care before and after organ transplantation. Conclusion Insulin purging in patients with AAN and T1DM poses severe health risks, including accelerated renal complications. For those considering transplantation, insulin purging has explicitly to be diagnosed and a holistic treatment addressing both the renal condition and psychosomatic symptoms/disorders is crucial for successful post-transplant outcomes.